2017
DOI: 10.1186/s12911-017-0574-6
|View full text |Cite
|
Sign up to set email alerts
|

Economic and organizational impact of a clinical decision support system on laboratory test ordering

Abstract: BackgroundWe studied the impact of a clinical decision support system (CDSS) implemented in a few wards of two Italian health care organizations on the ordering of redundant laboratory tests under different perspectives: (1) analysis of the volume of tests, (2) cost analysis, (3) end-user satisfaction before and after the installation of the CDSS.Methods(1) and (2) were performed by comparing the ordering of laboratory tests between an intervention group of wards where a CDSS was in use and a second (control) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…An assessment of the effect of electronic medical records-based clinical decision-support on HIV care in resource-constrained settings reported reductions in documentation errors, missed appointments, missed CD4 results, and waiting times [47]. An Italian study reported that introducing CDSS was associated with a 16% reduction in the number of inappropriate laboratory tests requested, which also reduced costs [48,49]. A cross-sectional study in northern Ghana showed that CDSS implementation was associated with reduced proportions of delivery complications and fewer maternal deaths [50].…”
Section: Computerised Decision-support and Performance-based Incentivesmentioning
confidence: 99%
“…An assessment of the effect of electronic medical records-based clinical decision-support on HIV care in resource-constrained settings reported reductions in documentation errors, missed appointments, missed CD4 results, and waiting times [47]. An Italian study reported that introducing CDSS was associated with a 16% reduction in the number of inappropriate laboratory tests requested, which also reduced costs [48,49]. A cross-sectional study in northern Ghana showed that CDSS implementation was associated with reduced proportions of delivery complications and fewer maternal deaths [50].…”
Section: Computerised Decision-support and Performance-based Incentivesmentioning
confidence: 99%
“…Die Implementierung von CDS-Systemen hat das Potenzial, Effizienz und Präzision der Versorgung zu verbessern, insbesondere in Disziplinen, die komplexe Entscheidungen erfordern. Clinical Decision Support kann zu Kostenersparnissen im Gesundheitssystem fĂĽhren [8], durch klinische Interventionen [9], durch die VerkĂĽrzung der stationären Verweildauer, durch den Vorschlag kostengĂĽnstigerer Medikamentenalternativen [10] oder durch die Reduzierung von Doppeluntersuchungen [11]. Die Vorteile umfassen neben einer Reduzierung unerwĂĽnschter Arzneimittelwirkungen [12] auch verringerte Mortalitätsrisiken [13].…”
Section: Nutzen Und Risiken Von Leitlinien Und Von Clinical Decisionunclassified
“…At first sight, these digital platforms seem to clearly outperform traditional approaches. However, the impact of their use on diagnostic precision, treatment efficacy, safety, quality of life and treatment costs needs to be objectivized and studied in more detail with regard to allergic diseases as it has been already done in other specialties and areas of medical care ( 70 – 73 ).…”
Section: Improving Monitoring and Prevention By Connecting Stakeholdementioning
confidence: 99%